Reaction of Methyl Thioacetate with Nitrilimines: An Experimental, Local Ionization Energy and Electrostatic Potential Investigation - ABU-AWWAD, FAKHR; ABU THAHER, BASSAM (Asian Journal of Chemistry, 2010)
The reaction of hydrazonoyl chloride [1] precursor of nitrilimines [2] with methyl thioacetate [3] proceeds away from the expected cycloaddition that aimed at obtaining 1,3,4-thiadiazine-5-one [4]. Unexpectedly, the final product was acyclic adduct. The reaction was computationally verified and compared with the reaction of nitrilimines [2] with α-aminoester [5] to give 4,5-dihydro-1,2,4-ttiazine- 6-ones [6]. For both reactions, the reactants, transition states and sought products were fully optimized using the HF/6-311G (d,p). Transition structures were tested in the existence of one imaginary vibrational frequency. Calculated minima of local ionization energy ( IS, min) and the extrema of electrostatic potential (VS, min , V S, max) of the reactants predicted and verified similar treuds in both reactions which indicate an analogous reactivity. and thus cyclic products [4, 6] are equally expected.